At a party, everyone shook hands with everybody else. There were 66 handshakes. How many people were at the party?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
nice thank u...
Nyc salution
SORACHA THAMMASIT 75000
as soon as you got 132 you can see it is 12 x 11
This actually gives the same result as the sum of a (1..n-1) series, if you cancel out n ! and ( n − 2 ) ! you get 2 n ( n − 1 ) = 6 6 Which is just amazing to me!
Let's say there are n people at the party. The first person shakes hands n-1 times, since he does not shake hands with himself. The next person then shakes hands with n-2 people (since he has already shaken hands with the first person), and so on until the last person has already shaken everyone's hand by the time it's his turn.
The total number of shakes for a party with n people is then given by 1+2+3+...+(n-1).
The formula for summation of integers 1 through x is (x)(x+1)/2. The total number of shakes at a party with n people is therefore (n-1)(n)/2. If we say (n-1)(n)/2 = 66, then we can solve for n to find that n = 12.
I thought the same way.
Same here bro
This is the approach I took.
66 "double" handshakes = 132 handshakes. 132 = 11 x 12, i.e. each of 12 people shakes hands with 11 other people.
This is very elegant.
lets say there are n persons first person shakes hand with everyone else: n-1 times(n-1 persons) second person shakes hand with everyone else(not with 1st as its already done): n-2 times 3rd person shakes hands with remaining persons: n-3 So total handshakes will be = (n-1) + (n-2) + (n-3) +…… 0; = (n-1) (n-1+1)/2 = (n-1) n/2 = 66 = n^2 -n = 132 =(n-12)(n+11) = 0; = n = 12 OR n =-11 -11 is ruled out so the answer is 12 persons.
you can use graph theory. A complete graph Kn(with n vertices) will have n(n-1))/2 edges. If we consider each handshake to be one edge, and n to be the number of people, then (n(n-1))/2=66 n(n-1)=66 x 2=132 n^2-n=132 n^2-n-132=0 (n-12)(n+11)=0 n=12 or n=-11(discard n=-11 as n >0) so there are 12 people at the party
Each person who arrives at the party shakes hands to everybody who arrived before; second shakes hands with first, thirth with first and second, and so on. Then you only have to add persons at first until the outcome is 66 handshakes. 1+2+3+4+5+6+7+8+9+10+11=66
Shaking with all the people is counting combination using n chosen 2 formula. n!/(n-2)!2 = n(n-1)/2 = 66. The only possible integer makes this formula satisfy if n = 12.
Recursive solution
Let h ( n ) be the total number of handshakes between n persons, then:
For an empty party, or if there is only one person: h ( 0 ) = h ( 1 ) = 0
If there are two persons: h ( 2 ) = 1
For n persons, person n shakes his hand with ( n − 1 ) persons: h ( n ) = n − 1 , but we must consider handshakes between everyone not only between one person to the others, so we can call recursively for ( n − 1 ) persons, so we get the recurrence:
{ h ( 0 ) = 0 h ( n ) = h ( n − 1 ) + ( n − 1 )
Find a closed form:
h ( n ) = h ( n − 1 ) + ( n − 1 ) = h ( n − 2 ) + ( n − 2 ) + ( n − 1 ) = h ( 0 ) + ( 1 − 1 ) + . . . + ( n − 2 ) + ( n − 1 ) = k = 1 ∑ n ( n − k ) = k = 1 ∑ n n − k = 1 ∑ n k = n 2 − 2 n ( n + 1 ) = 2 n ( n − 1 )
Then, for 66 handshakes:
2 n ( n − 1 ) = 6 6 ⇒ n 2 − n − 1 3 2 ⇒ n = 1 2
Let us say there are n people at the party, each person will shake the rest of (n-1) person. since A shakes B equals to B shakes A, (A B C: AB AC BA BC CA CB) so by n*(n-1) we have double counted the number of handshakes. Therefore n(n-1)/2 = 66, so n =12.
Amount of connections in the network of N subjects can be calculated as SQR(N) minus the summation of all numbers from 1 to N. You can use this formula to find the right answer as well
Just start counting your way to the top.
1+2+3+4=10
10+5+6=21
21+7+8+9=21+3×8=45
45+10+11=66
But you don't shake hands with yourself (unless you're lonely)
So we have to do 11+1=12 (too difficult?)
There is a further simple method to do this , just plug in the values in the formula : 2 n ( n + 1 ) where n is the total number of hand shakes
solving this => n 2 − n − 1 3 2 = 0
= ( n + 1 1 ) ( n − 1 2 )
=> n=12 (ignoring the negative value since it is meaningless )
n cannot be the total number of handshakes, as you states but of people in the party (though you then go on calculating correctly that n=12 is the number of people).
Rewriting the required as to find n , where n C 2 = 6 6 . ∴ 2 ! n P 2 = 6 6 ∴ n P 2 = 1 3 2 = 1 2 × 1 1 = 1 2 P 2 ∴ n = 1 2 .
There is n people in the party. Everyone shakes hands with everyone ELSE, so everyone shakes hands with n - 1 people. There is n(n-1) handshakes, but this amount must be halved, because if person A shakes hands with person B it is same as if person B shakes hands with person A, so total amount of handshakes is n(n-1)/2. We know that total number of handshakes is 66, so n(n-1)/2 = 66 n^2 - n = 132 n^2 - n - 132 = 0 (n + 11)(n - 12) = 0 So solutions are -11 and -(-12)=12. Number of handshakes must be positive, so 12 is only solution left.
Result: 12
Here's the way that I did it, although there are more effective ways of doing it.
I figured out in my head that:
2 people = 1 hand shake 3 people = 3 hand shakes 4 people = 6 hand shakes 5 people = 10 hand shakes
Then I noticed the pattern and just kept adding up the pattern until I got to 66 handshakes.
66 can factorized as = 11 x 6 = 11 x 12 / 2 = 12 = handshake problem = n(n-1)
Problem Loading...
Note Loading...
Set Loading...
This can be solved using combinations where handshakes can be considered as a selection of 2 people where the order doesn't matter.
Therefore by writing the combination n C 2 in factorials form we have:
2 ! . ( n − 2 ) ! n ! = 6 6
By multiplying both sides by [ 2! ] we get:
( n − 2 ) ! n ! = 1 3 2
Then we can expand the numerator factorial so it becomes:
( n − 2 ) ! n . ( n − 1 ) . ( n − 2 ) ! = 1 3 2
by cancelling ( n − 2 ) ! and distributing n on the bracket ( n − 1 ) we get:
n 2 − n − 1 3 2 = 0
Factorizing this:
( n + 1 1 ) ( n − 1 2 )
Therefore n is -11 or 12, (-11 is refused because n cannot be a negative number)